Malignant transformation of oral leukoplakia: Systematic review and meta‐analysis of the last 5 years - Aguirre‐Urizar, José M.; Lafuente‐Ibáñez de Mendoza, Irene; Warnakulasuriya, Saman (Oral diseases, 2021)
Objective Oral leukoplakia (OL) is the most frequently encountered oral potentially malignant disorder. The aims of this systematic review are to estimate the overall malignant transformation of OL and to assess the risk factors associated with malignant transformation of OL published in the last 5 years (2015–2020). Materials and Methods We performed a bibliographic search in PubMed, Scopus, Web of Science, Embase, and Cochrane databases with keywords “oral leukoplakia”, “oral cancer”, “oral carcinoma” and “oral squamous cell carcinoma”. Meta‐analysis was conducted using a random‐effects model. Results Twenty‐four studies were selected, that reported a total of 16,604 patients. Malignant transformation proportion varied between 1.1% and 40.8%. Female gender, non‐homogeneous clinical type, and presence of epithelial dysplasia were significantly related to MT. Other risk factors previously suggested did not show significant results. Conclusions The pooled proportion of malignant transformation MT was 9.8% (95% CI: 7.9–11.7). It is necessary to continue to conduct well‐designed prospective clinicopathological studies on OL, using a uniform definition for OL to reduce the risk of bias for evaluating various factors associated with the MT.